2020
DOI: 10.1111/tbj.14093
|View full text |Cite
|
Sign up to set email alerts
|

Oncoplastic breast‐conserving therapy and intraoperative radiotherapy for management of carcinoma in situ of the breast: A single‐center experience

Abstract: Intraoperative radiation therapy (IORT) has been shown to reduce local recurrence rates among women with early‐stage invasive ductal carcinoma, but data regarding its use among women with in situ carcinoma are limited. In this single‐institution study, 50 women with in situ carcinoma were treated with oncoplastic breast‐conserving surgery (OPS) and single‐dose IORT. All 50 patients had “no tumor on ink,” but 9 (16%) had margins < 2 mm and required additional therapy. No local recurrences were observed after a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…A 2019 study by Van la Parra and colleagues examined a large case series of 68 patients and found a positive margin rate of 14.7%, significantly related to a tumor size larger than 5 cm [ 9 ]. Finally, a recent study by Crown et al reported a 16% close margins rate, although none of the 50 patients presented focally involved margins, and no recurrences were noted during a median follow-up of 46 months [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2019 study by Van la Parra and colleagues examined a large case series of 68 patients and found a positive margin rate of 14.7%, significantly related to a tumor size larger than 5 cm [ 9 ]. Finally, a recent study by Crown et al reported a 16% close margins rate, although none of the 50 patients presented focally involved margins, and no recurrences were noted during a median follow-up of 46 months [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Breast-conserving surgery (BCS) has also expanded thanks to the use of level II oncoplastic techniques, which allow for resections of large lesions involving up to 50% of the total breast volume, without compromising the final breast cosmesis [ 6 ]. These techniques have reduced both the mastectomy and re-excision rates; however, their use in the management of DCIS was reported in only a few studies, with a small series of patients [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, breast conserving surgery [BCS] plus radiation therapy is widely accepted as an alternative as it is equally safe as mastectomy. This progress, together with the use of intraoperative radiation therapy [IORT], the introduction of skin/nipple sparing methods, and the oncoplastic repair of huge surgical defects, has led to the need for intraoperative information regarding the margin status [3] .…”
Section: Introductionmentioning
confidence: 99%
“… 2 Although surgery plus intra-operative radiotherapy is emerging as a new treatment option for DCIS, the main treatment methods are still mastectomy and breast conservation surgery(BCS) with or without radiotherapy. 3 - 5 In a large population study from the United Kingdom, the percentage of patients who received only BCS, BCS plus radiotherapy, and mastectomy were 26.3%, 40.4%, and 29.8%, respectively. Furthermore, mastectomy was found to be performed more commonly in patients with a tumor of high-grade (36%) compared to that of low-grade (15%).…”
Section: Introductionmentioning
confidence: 99%